Fungsi Koordinasi Kedinasan Terhadap Pelaksanaan Kerjasama Pada Dinas Transmigrasi Kabupaten Buton - Hardi, Hartina; Banga, Wempy; Kadir, Abdul (REZ PUBLICA, 2020)
The research objective was to determine the coordination function of official staff and the factors that influence coordination at the Buton Regency Transmigration Service. Data collection techniques used in this study are by means of library research and field research using observations (observation), interviews and documentation. The results of the research show that the implementation of the coordination function is quite well done where in the completion of an activity it has run optimally in accordance with what has been planned and in accordance with the main tasks that have been determined and the factors that affect coordination can be adjusted to the activities that occur in the transmigration office which makes every existing activity can be carried out quite well even though there are still obstacles that occur